EFFECT OF HYDROGEN LIMITATION AND TEMPERATURE ON THE FRACTIONATION OF SULFUR ISOTOPES BY A DEEP-SEA HYDROTHERMAL VENT SULFATE-REDUCING BACTERIUM - Hoek J.; Reysenbach A.L.; Habicht K.S.; Canfield D.E. (My University, 2006)
The fractionation of sulfur isotopes by the thermophilic chemolithoautotrophic Thermodesulfatator indicus was explored during sulfate reduction under excess and reduced hydrogen supply, and the full temperature range of growth (40-80 °C). Fractionation of sulfur isotopes measured under reduced H2 conditions in a fed-batch culture revealed high fractionations (24-37?) compared to fractionations produced under excess H2 supply (1-6?). Higher fractionations correlated with lower sulfate reduction rates. Such high fractionations have never been reported for growth on H2. For temperature-dependant fractionation experiments cell-specific rates of sulfate reduction increased with increasing temperatures to 70 °C after which sulfate-reduction rates rapidly decreased. Fractionations were relatively high at 40 °C and decreased with increasing temperature from 40-60 °C. Above 60 °C, fractionation trends switched and increased again with increasing temperatures. These temperature-dependant fractionation trends have not previously been reported for growth on H2 and are not predicted by a generally accepted fractionation model for sulfate reduction, where fractionations are controlled as a function of temperature, by the balance of the exchange of sulfate across the cell membrane, and enzymatic reduction rates of sulfate. Our results are reproduced with a model where fractionation is controlled by differences in the temperature response of enzyme reaction rates and the exchange of sulfate in and out of the cell.
Keywords: ENZYME ACTIVITY; HYDROGEN SULFIDE; HYDROTHERMAL VENT; ISOTOPIC FRACTIONATION; REDUCTION; SULFATE-REDUCING BACTERIUM; SULFUR ISOTOPE; TEMPERATURE EFFECT; THERMOPHILIC BACTERIUM; BACTERIA (MICROORGANISMS); THERMODESULFATATOR INDICUS